THE IMPACT OF ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (e-CRM) FEATURES ON e-LOYALTY AMONG ONLINE PURCHASERS: THE MEDIATING ROLE OF e-CUSTOMER SATISFACTION (Journal of Technology and Operations Management, 2025)
In the current digital business landscape, the shift towards e-commerce has resulted in intense competition among companies, posing a significant challenge to e-loyalty. Factors such as limited real-time responses, poor network connectivity, and inadequate website elements hinder e-customer satisfaction and e-loyalty in online purchases. Therefore, this research aims to determine the level of e-customer satisfaction with eCRM features, identify the impact of e-CRM features on e-loyalty among online purchases, and examine the mediating role of e-customer satisfaction in the relationship between e-CRM features and e-loyalty in online purchasing. The study utilized SPSS and AMOS software for data analysis using responses from 384 Malaysian citizens in areas of Selangor and Kuala Lumpur who have experience with online purchases. The data were collected through an online survey using Google Forms. The study found out all attributes of e-CRM features had a significant relationship with e-customer satisfaction, but e-sales and e-support did not have found significant correlation with e-loyalty. This study also finds a positive relationship between the mediating role of e-customer satisfaction and the relationship between e-CRM and e-loyalty among online purchases. In conclusion, the study provides a clear overview of customer trends with online purchases through e-CRM features. Besides that, the study also provides an understanding of significant e-CRM features to enhance e-loyalty through e-customer satisfaction for e-commerce.